UTILIZING ENOXAPARIN IN THE MANAGEMENT OF ACUTE CORONARY SYNDROME - O. V. Krikunova; R. I. Stryuk (Столичная издательская компания, 2018)
Anticoagulant therapy is widely used in all forms of acute coronary syndrome (ACS) to inhibit the formation of thrombin and/or to inhibit its activity to reduce the risk of thrombotic events (both in primary percutaneous coronary intervention and in the absence of revascularization). Of the entire range of anticoagulants offered by the domestic and foreign pharmaceutical industry, a limited number of drugs of this group are used in the treatment of ACS, in particular, unfractionated heparin and low molecular weight heparin - enoxaparin.Enoxaparin has a safety profile and clinical efficacy at least comparable to that of unfractionated heparin, and at the same time has a number of obvious advantages, such as a simpler protocol of administration and dosing, does not require routine monitoring of the parameters of the blood coagulation system. In patients with ACS with ST-segment elevation the routine administration of enoxaparin should be considered as an alternative to the standard regimen of unfractionated heparin therapy. In patients with ACS without ST-segment elevation enoxaparin should be used when fondaparinux is unavailable.